World trade law after neoliberalism re-imagining the global economic order - Lang, Andrew (Oxford : Oxford University Press, 2011)
It is often argued that there is an inherent tension between human rights law and the rules of free trade. This book explores the assumptions underlying this debate and argues that we need to reconsider them, focusing more on how expert knowledge and informal relationships shape trade law and its interaction with human rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Trade regulation; Human rights -- Economic aspects; World Trade Organization; Neoliberalism